ROLE OF EDUCATION IN SOCIO-CULTURAL CHANGES - Elmuradova Surayyo Abdijalilovna (Web of Journals Publishing, 2024)
This article highlights the role and importance of education in socio-cultural changes, as well as some ways in which education can contribute to cultural changes.
Keywords: education, gender, cultural consciousness, cultural practices, mother tongue, socialization and norms.